2019
DOI: 10.1002/ijc.32623
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of antibody responses to nonviral cancer antigens in head and neck squamous cell carcinoma patients differ by human papillomavirus status

Abstract: There have been hints that nonviral cancer antigens are differentially expressed in human papillomavirus (HPV)‐positive and HPV‐negative head and neck squamous cell carcinoma (HNSCC). Antibody responses (AR) to cancer antigens may be used to indirectly determine cancer antigen expression in the tumor using a noninvasive and tissue‐saving liquid biopsy. Here, we set out to characterize AR to a panel of nonviral cancer antigens in HPV‐positive and HPV‐negative HNSCC patients. A fluorescent microbead multiplex se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
(76 reference statements)
0
9
0
2
Order By: Relevance
“…Here, finding optimal gene subsets such as target selection for semi-personalized vaccination is formulated as a multi-objective optimization task. We further presented a walkthrough for the use of AVAtar by showing a real case scenario already applied in medical research [ 29 ]. The analysis of HNSCC expression data demonstrates the capabilities of AVAtar focusing on data import, visualization and optimization.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Here, finding optimal gene subsets such as target selection for semi-personalized vaccination is formulated as a multi-objective optimization task. We further presented a walkthrough for the use of AVAtar by showing a real case scenario already applied in medical research [ 29 ]. The analysis of HNSCC expression data demonstrates the capabilities of AVAtar focusing on data import, visualization and optimization.…”
Section: Discussionmentioning
confidence: 99%
“…In the following sections, we will further guide through the features of AVAtar by presenting the use case also available on the tutorial of the software. An in-depth medical description of the analysis performed on AVAtar can be found in [ 29 ]. The HNSCC analysis aims is to compare promising vaccination target sets for different subgroups of patients with HNSCC.…”
Section: Use Case: Vaccination Targets For Hnsccsmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence from some studies suggests that CT antigens are present and recognized by the immune system in HPVpositive HNSCC patients and may serve as prognostic biomarkers. One study examining antibody responses to 16 CT antigens in HNSCC patients identified a subset of HPV-positive patients who exhibited responses, although there was considerable heterogeneity in the target signatures [136]. A related study examined prognostic trends in HNSCC patient antibody responses to 16 CT antigens, stratified by HPV status.…”
Section: Ct Antigen Expression In Hpv-positive Hnsccsmentioning
confidence: 99%